2016
DOI: 10.1007/s12035-016-0035-8
|View full text |Cite
|
Sign up to set email alerts
|

Late Maternal Folate Supplementation Rescues from Methyl Donor Deficiency-Associated Brain Defects by Restoring Let-7 and miR-34 Pathways

Abstract: The micronutrients folate and vitamin B12 are essential for the proper development of the central nervous system, and their deficiency during pregnancy has been associated with a wide range of disorders. They act as methyl donors in the one-carbon metabolism which critically influences epigenetic mechanisms. In order to depict further underlying mechanisms, we investigated the role of let-7 and miR-34, two microRNAs regulated by methylation, on a rat model of maternal deficiency. In several countries, public h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 79 publications
2
34
0
Order By: Relevance
“…Behavioral evaluation was performed on rat pups. A homing test was conducted as described previously to monitor basic learning functions. An Aquatic Multiple T‐Maze was used to evaluate learning performances in adults, and consisted of a modified Morris Water Maze .…”
Section: Methodsmentioning
confidence: 99%
“…Behavioral evaluation was performed on rat pups. A homing test was conducted as described previously to monitor basic learning functions. An Aquatic Multiple T‐Maze was used to evaluate learning performances in adults, and consisted of a modified Morris Water Maze .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a deceased status in methyl donors is correlated to accelerated cognitive decline and senescence [29][30][31]. Actually, studies using animal models showed the efficiency of supplementations on plasma and body parameters, attesting to a restoration of healthy conditions for animals initially subjected to various methyl-donor deficiencies [28,[32][33][34]. Nevertheless, at least two questions remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Further complexity is introduced by increases in the flow of lipids through the liver, a product of both excess in the mother's diet and mobilisation of excess body fat. Analysis of fetal tissues suggests that methyl deficiency produces changes in the fetal liver (79,80) heart (81) , gut (82) and brain (83,84) . Measurements of methionine flux show that methyl metabolism is protected in the late gestation fetus (75) suggesting that it is the deficiency or excess of the products of folate-dependent metabolism that influences the regulation of gene expression (81) .…”
Section: Impact Of Limited C 1 Metabolism On the Metabolism Of The Momentioning
confidence: 99%